Structural method of analysis of information education system - Шибицкий, В. П. (Proceedings of National Aviation University (archive), 2000)
Proposed is a multiple model of didactic knowledge which allows to apply decomposition methods and multisequencing for construction of more efficient algorithms of didactic knowledge and formation of influences in the form of information objects stream<!–EndFragment–> pan>